(untitled) (Progressive Agriculture, 2016)
Drought adversely affects growth and yield of crops to various extents. Growing of drought tolerant crops is a good option to obtain economical yields from water stress areas for which quick method to screen drought tolerant plants, particularly in early stages of their growth is important. For this reason, a field experiment was conducted to evaluate the genetical potential to drought tolerance of four sorghum varieties viz Hybrid Sorgo, Safal, BD 731, BD 740. The experiment was laid out in a split plot design with three replications. The plants were grown under three drought levels viz. 100% FC (control), 70% FC and 40% FC. Growth and yield of the Sorghum varieties were found to be decreased gradually with gradual increase in drought levels as compared to the control. This reduction was associated with decreased yield components. Water stress also decreased protein and starch content. The variety BD 740 followed by BD 731 showed the better performance in respect of no. of grains panicle-1, panicle dry weight, 1000-grain weight, grain yield hill-1, protein content and starch content than Hybrid Sorgo and Safal at same water stress condition. Therefore Bangladeshi varieties were found more tolerant than Hybrid Sorgo variety to water stress. Findings of this research will be helpful for the farmers about the beneficial use of resource in terms of managing limited water as well as increasing crop productivity. Finally these research findings would certainly contribute food security in Bangladesh. Progressive Agriculture 27 (3): 265-271, 2016